Re:Learn: Creating an online course to facilitate collaborative learning on student information literacy - Eriksson, Marie-Louise; Borg, Linda (Septentrio Conference Series, 2020)
Today many librarians and writing tutors are teaching information literacy in higher education. How can we facilitate collaboration on questions regarding this teaching? How do we relate our teaching to various national and international frameworks and guidelines? Is it possible to create a platform for the exchange of ideas and tools? How do we develop new methods for writing tutors and librarians to collaborate? These are some of the questions that led us to start this project: to develop an open web course on student learning and information literacy in higher education. But instead of targeting students in higher education the target group for this course is teaching librarians and writing tutors at Swedish universities. The project is funded by the Swedish Library Association. The purpose of the course is to: Place information literacy (where academic writing and information seeking both are natural components) in an academic context Develop national collaborationon issues related to the teaching of information literacy and academic writing To facilitate online peer learning between colleagues on issues related to teaching information literacy and academic writing Develop a platform for sharing experiences and best of practices regarding tools and working methods Strengthen the digital competence in the professions The participants in the course will get the opportunity to engage in inspirational workshops and PBL-inspired group work on for example flipped teaching, active learning, digitization issues and open networked learning with a focus on information literacy. In this way we hope to facilitate a creative and collaborative learning environment regarding the teaching of information literacy in higher education. The first iteration of the course will take place in October-December 2020 and will be held in Swedish. This presentation will be about the planning and development of the course. We will present the work done so far and look forward to feedback and input to the ongoing work.